2021
DOI: 10.1108/jhti-03-2021-0062
|View full text |Cite
|
Sign up to set email alerts
|

Green meets social media: young travelers’ perceptions of hotel environmental sustainability

Abstract: PurposeA competitive hospitality environment requires attracting new target markets. The purpose of this research is to investigate how young travelers’ intention to stay and electronic word-of-mouth (eWOM) are impacted by a hotel’s environmental sustainability communications on social media.Design/methodology/approachThe data were collected from 306 participants via online survey and analyzed in SPSS and AMOS. Structural equation modeling was utilized for hypotheses testing.FindingsThe results support the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…From the consumer perspective, it is conceivable to claim that the qualifications especially sought by the millennium generation should be taken into consideration by hoteliers. As a result of their research, Clark et al (2021) revealed that when hotels convey their messages about sustainability through social media, they attract the attention of young consumers more. Wang et al (2020) found that the millennium generation has the higher intention for green consumption and they attach more importance to green consumption when making travel decisions.…”
Section: Resultsmentioning
confidence: 99%
“…From the consumer perspective, it is conceivable to claim that the qualifications especially sought by the millennium generation should be taken into consideration by hoteliers. As a result of their research, Clark et al (2021) revealed that when hotels convey their messages about sustainability through social media, they attract the attention of young consumers more. Wang et al (2020) found that the millennium generation has the higher intention for green consumption and they attach more importance to green consumption when making travel decisions.…”
Section: Resultsmentioning
confidence: 99%
“…In the hospitality and tourism technology literature (Arica et al , 2022; Clark et al , 2021; Dastjerdi et al , 2019; Fakfare, 2021), discussions are generally limited to comprehend the general facet of travel app contents that influence app usage intention and the attractiveness of travel apps. No agreement was found regarding the appropriate scales for measuring the quality of travel apps, particularly from the perspective of app contents.…”
Section: Discussionmentioning
confidence: 99%
“…As for the Elaraby Group website did not pay any attention to highlighting its development activities and did not specify any tab to show these practices. The website is nothing but a store for displaying electronic products that it promotes for sale (5) .…”
Section: Among the Digital Marketing Activities And Means That The El...mentioning
confidence: 99%